2000
DOI: 10.1007/s100720070100
|View full text |Cite
|
Sign up to set email alerts
|

Does abnormal neuronal excitability exist in myotonic dystrophy)?�II. Effects of the antiarrhythmic drug hydroquinidine on apathy and hypersomnia

Abstract: An abnormal neuronal excitability in myotonic dystrophy (MD) might contribute to psychomotor and behavioral disturbances of MD patients. To gain new insights into the pathophysiology of MD, we determined whether the antiarrhythmic drug hydroquinidine could ameliorate apathy and hypersomnia besides slow saccadic eye movements in these patients. The study was conducted in a randomized, placebo-controlled, double-blind, crossover manner. Ten ambulatory patients without contraindications to hydroquinidine administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…Findings also confirm the absence of relationship between apathy and age, gender, disease duration, CTG repeats, functional impairment, and fatigue in DM1 patients [ 13 , 14 ]. The absence of a significant correlation between apathy and fatigue must be pointed out considering the conceptual proximity of lack of motivation and experienced fatigue [ 30 ].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Findings also confirm the absence of relationship between apathy and age, gender, disease duration, CTG repeats, functional impairment, and fatigue in DM1 patients [ 13 , 14 ]. The absence of a significant correlation between apathy and fatigue must be pointed out considering the conceptual proximity of lack of motivation and experienced fatigue [ 30 ].…”
Section: Discussionsupporting
confidence: 67%
“…In addition, they found that apathy did not vary with duration of illness, muscular weakness, depression, daytime sleepiness, and fatigue. The absence of relationship between apathy and depression was also noted in a subsequent smaller study ( n = 10 DM1 patients) looking at an anthiarrhytmic drug [ 14 ]. No study has though explored the relationship of apathy to cognitive abilities in DM1 patients.…”
Section: Introductionmentioning
confidence: 70%
“…The global layer also includes myosine heavy chain isoforms of the same type as in the heart muscle (Alfa‐cardic myosi). Treatment for antiarrhythmia has shown to have an effect on slow saccades, and thus ocular motor analysis may be useful for follow up in patients with DM1 (Di Costanzo et al. 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Caughey and Myrianthopoulos noted that affected individuals, even when mildly incapacitated physically, are often content to sit or lie idle for hours [55]. The prevalence of apathy in DM1 varies across studies (40-90%) [56][57][58].…”
Section: Apathy In Dm1mentioning
confidence: 99%